The Extent, Nature and Distribution of Child Poverty in India. Issue 1 (April 2016) - Gordon, David; Nandy, Shailen
Despite a long history, research on poverty has only relatively recently examined the issue of child poverty as a distinct topic of concern. This article examines how child poverty and well-being are now conceptualized, defined and measured, and presents a portrait of child poverty in India by social and cultural groups, and by geographic area. In December 2006, the UN General Assembly adopted a definition of child poverty which noted that children living in poverty were deprived of (among other things) nutrition, water and sanitation facilities, access to basic health care services, shelter and education. The definition noted that while poverty hurts every human being 'it is most threatening and harmful to children, leaving them unable to enjoy their rights, to reach their full potential and to participate as full members of the society'. Researchers have developed age-specific and gender-sensitive indicators of deprivation which conform to the UN definition of child poverty and which can be used to examine the extent and nature of child poverty in low and middle-income countries. These new methods have 'transformed the way UNICEF and many of its partners both understood and measured the poverty suffered by children' (UNICEF, 2009). This article uses these methods and presents results of child poverty in India based on nationally representative household survey data for India.